Smart indoor LED lighting design powered by hybrid renewable energy systems - ORAL, BÜLENT; KIYAK, İSMAİL; TOPUZ, VEDAT (ELSEVIER SCIENCE SA, 2017)
It's important to provide diversity in energy resources and to use sustainable energy resources besides local resources. In the recent years, LEDs have been increasingly used in interior lighting systems because of their low energy consumption, high light-flux efficiency and their ability to maintain the light-flux value at a constant level for a long period of time. In this study, a LED luminaire was designed by using the Osram Coinstar W4 brand power LED module. An LED drive card, which is a specialty of the luminaire, was designed to provide ideal functioning conditions and serve as a power supply for the LEDs. A communication card was designed for all kinds of information exchange between the LED luminaires, motion detectors and light sensors used with the laboratory lighting system, and an RS485 communication line was installed to connect every system. Under the control of the luminaire, the lighting was tested by a fuzzy-expert system. With this project design and test, a system was developed that can be used in interior spaces. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: LED indoor lighting; Building-integrated renewable energy systems; Intelligent lighting; Energy saving